(untitled) (Journal of Fiber Bioengineering and Informatics, 2012)
The moisture transmission behaviour of clothing plays an important role in determining its thermo- physiological comfort. The determination of the factors involved in moisture transmission of clothing and its prediction have become a main concern for researchers for many years. An attempt has been made to review the research studies on modeling and simulation of moisture transmission through fibrous assemblies. The review work has been divided in two parts. The first part deals with moisture vapour transmission and the second with liquid water transmission through fibrous materials. The various processes involved in water vapour transmission through fibrous materials are diffusion, absorption - desorption, convection, evaporation and condensation. The models on water vapour transmission through fibrous materials are based on the mass balance equation. Some of the studies involving theoretical work on vapour transmission have been conducted on individual processes. Others consider the inter-related effects involved. Moisture vapour transmission through textile materials is coupled with heat transfer phenomena, due to its hygroscopic nature. The atmospheric conditions, the structure of the fibrous materials and the hygroscopic nature of the fibres significantly influence the processes. Amongst the available models on vapour transmission, the model developed by Li and Zhu predicts simultaneous heat and moisture transfer considering moisture sorption, condensation and capillary liquid diffusion in porous textiles and this model is best suited for determining textile clothing comfort.